Saffron Stigmas Apocarotenoid Contents from Saffron Latent Virus (SaLV)-Infected Plants with Different Origins and Dehydration Temperatures - Cándida Lorenzo; Golnaz Shadmani; Hajar Valouzi; Natalia Moratalla-López; Habibullah Bahlolzada; Rosario Sánchez-Gómez; Akbar Dizadji; Gonzalo L. Alonso (Horticulturae, 2023)
Saffron is a spice that is obtained by dehydrating the stigmas of the Crocus sativus flower. Iran is the country that produces the largest amount of saffron, exceeding 90% of world production. Currently, there is a growing medicinal use which implies that there is more demand than supply worldwide, in turn, a large amount of labor is required to obtain it; for these two reasons, it reaches a high price in the international market. This demand is due to the high concentration of apocarotenoid metabolites that it biosynthesizes. In this work, the content of these metabolites of saffron from six production areas of Iran and neighbouring countries infected with saffron latent virus (SaLV) and dehydrated at two temperatures is compared. The corms of the six provenances were planted in a homogeneous plot and the stigmas analyzed were those of the second year after planting. The analysis showed that corms do not completely retain the memory of their original origin. In general, the ratio of the sum of mmol/kg of HTCC derivatives to the sum of the mmol of crocins is greater than two. This implies that the biosynthesis of saffron apocarotenoids due to the degradation of β-carotene towards HTCC is more important than that of zeaxanthin formation, which later gives HTCC and crocetin dialdehyde.